Reading the Archive of Earth's Oxygenation Volume 3: Global Events and the Fennoscandian Arctic Russia - Drilling Early Earth Project - Melezhik, Victor; Prave, Anthony R.; Hanski, Eero J.; Fallick, Anthony E.; Lepland, Aivo; Kump, Lee R.; Strauss, Harald (Frontiers in Earth Sciences,, 2013)
Earth's present-day environments are the outcome of a 4.5 billion year period of evolution reflecting the interaction of global-scale geological and biological processes. Punctuating that evolution were several extraordinary events and episodes that perturbed the entire Earth system and led to the creation of new environmental conditions, sometimes even to fundamental changes in how planet Earth operated. Volume 3: Global Events and the Fennoscandian Arctic Russia - Drilling Earth Project represents another kind of illustrated journey through the early Palaeoproterozoic, provided by syntheses, reviews and summaries of the current state of our understanding of a series of global events that resulted in a fundamental change of the Earth System from an anoxic to an oxic state. The book discusses traces of life, possible causes for the Huronian-age glaciations, addresses radical changes in carbon, sulphur and phosphorus cycles during the Palaeoproterozoic, and provides a comprehensive description and a rich photo-documentation of the early Palaeoproterozoic supergiant, petrified oil-field. Terrestrial environments are characterised through a critical review of available data on weathered and calichified surfaces and travertine deposits. Potential implementation of Ca, Mg, Sr, Fe, Mo, U and Re-Os isotope systems for deciphering Palaeoproterozoic seawater chemistry and a change in the redox-state of water and sedimentary columns are discussed. The volume considers in detail the definition of the oxic atmosphere, possible causes for the oxygen rise, and considers the oxidation of terrestrial environment not as a single event, but a slow-motion process lasting over hundreds of millions of years. Finally, the book provides a roadmap as to how the FAR-DEEP cores may facilitate future interesting science and provide a new foundation for education in earth-science community. Welcome to the illustrative journey through one of the most exciting periods of planet Earth!